Pengaruh Efikasi Diri dan Lokus Kendali Terhadap Kinerja ASN Melalui Learning Agility - Nadu, Finsensius; Se, Hyronimus (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
The objectives of this study, namely (1) To analyze the effect of self-efficacy on performance of the State Civil Apparatus (ASN) in Ende Regency; (2) To analyze the effect of locus of control on the performance of the State Civil Apparatus in Ende Regency ; (3) To analyze the effect of learning agility on the performance of the State Civil Apparatus (ASN) in Ende Regency and performance of the State Civil Apparatus (ASN) in Ende Regency; (4) To analyze the mediating role of learning agility in the relationship between self-efficacy on the performance of the State Civil Apparatus ASN) in Ende Regency; and (5) To analyze the mediating role of learning agility in the relationship between the locus of control and the performance of the State Civil Apparatus (ASN) in Ende Regency. agility in the relationship between locus of control on the performance of the State Civil Apparatus (ASN) in Ende Regency. (ASN) in Ende Regency. This research uses quantitative methods. The population in this study amounted to 4,674 and the sample of this study amounted to 318 respondents. The type of data used is quantitative data. Data sources used primary data and secondary data. This research uses smart PLS. The results of The results of this study, namely (1) self-efficacy has no effect on the performance of the State Civil Apparatus (ASN) in Ende Regency performance of the State Civil Apparatus (ASN) in Ende Regency; (2) locus of control affects the performance of the State Civil Apparatus (ASN) in Ende Regency; (3) learning agility has an effect on the performance of the State Civil Apparatus (ASN) in Ende Regencyon the performance of the State Civil Apparatus (ASN) in Ende Regency; (4) learning agility cannot mediate the effect between self-efficacy on performance, and (5) learning agility can mediate the effect between self-efficacy and performance. learning agility can mediate the effect between locus of control on performance.